Pauperization and migration: the continuing violence of green revolution in rural Punjab, Pakistan - Nadir, Rabia; Batool, Fizza; Javaid, Huda; Ghazanfar, Munir; Bashir, Soha; Naeem, Huma (Aktuelle Forschungsbeiträge zu Südasien, 2024)
Female migration, Punjab, Green Revolution, poor peasants, maids, agrarian change
Keywords: Hausgehilfin; Landflucht; Armut; Industrialisierung; Landwirtschaft; Punjab